Analysis of APILL Interchange Capacity, Effective Approach Width, and Saturation Current Determination Using PKJI 2023. - Legio Pranata, Billy; Pratama, Galih; Gagas, Gregorius; Sutrisno, Widarto; Wahyu Gutama, Detha Sekar Langit (Winter Journal: IMWI Student Research Journal, 2023)
In this research, data analysis uses the 2023 Indonesian Road Capacity Guidelines (PKJI) method to produce signalized intersection performance data including capacity, level and level of congestion, delays, impact of vehicle emissions as well as queue capacity and service level at the intersection. intersection. The results of this research can be used to re-plan routes so that route segment performance can operate optimally. This research requires primary and secondary data. Primary data was collected by conducting direct field surveys, while secondary data was obtained from relevant government agencies. Primary Data Collection is data obtained from the results of field surveys. The data includes: a. Environmental and geometric conditions at each intersection b. Vehicle volume is calculated using CCTV at each intersection. c. Calculating Determination of Effective Approach Width. d. Calculating Determination of saturation current. 3.2 Secondary Data Collection This secondary data is data obtained from related agencies, in the form of population data and traffic data on Jl.KH. Wahid Hasyim and Jl. Sewer Inspection Mataram, Dabag, Condongcatur, Sleman, DIY. Based on the results of research conducted at the empang intersection, Jl. KH. Wahid Hasyim and Jl. Mataram Sewer Inspection, Dabag, Condongcatur, Sleman, DIY. On Sunday 01/10/2023, Monday 02/10/2023, Tuesday 03/10/2023, Wednesday 04/10/2023, Thursday 05/10/2023, Friday 06/10/2023 and Saturday 07/10/2023 . It can be concluded that the busiest traffic activity occurred on Monday, 02/10/2023. With a total of 2539 vehicles or 1106.2 SMP/Hour. High traffic volume is a problem that must be addressed. Based on the analysis carried out at the intersection, the following conclusions can be drawn: 1. Vehicle volume based on the results of a 7 day traffic survey at the intersection of four KH roads. Wahid Hasyim and the Mataram Sewer Inspection Road obtained results of a heavy number of vehicles on Monday 02/10/2023 for the time period 06.00 – 07.00 and 16.30 – 17.30. namely 2539 Kend/Hour. 2. KH four-way intersection capacity. Wahid Hasyim and the Mataram Sewer Inspection road for the period Monday 02/10/2023 in the north direction 1315.811775 SMP/hour, south 1307.86199 SMP/hour, east 2325.226635 SMP/hour, west 2190.930622 SMP/hour. 3. Effective Approach Width on KH road. Wahid Hasyim and the Mataram Sewer Inspection road in the north direction 16.5m, south 13.3m, east 12m, west 10.5m. 4. Basic saturated current on KH road. Wahid Hasyim and the Mataram sewer inspection road in the north direction 9900 SMP/hour, south 7980 SMP/hour, east 7200 SMP/hour, west 6300 SMP/hour. 5. Adjusted saturation current J on road KH. Wahid Hasyim and the Mataram Sewer Inspection road in the north direction 9556.948685 SMP/hour, south 7847.171942 SMP/hour, east 6827.261184 SMP/hour, west 6170.376038 SMP/hour.